1996
DOI: 10.1128/iai.64.10.4307-4312.1996
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi induces secretion of pro-urokinase-type plasminogen activator by human monocytes

Abstract: Borrelia burgdorferi is transmitted by infected ticks and causes Lyme disease. To infect distant organ sites, B. burgdorferi spirochetes must disseminate from the site of the tick bite. During dissemination from the dermal tissue, they breach tissue barriers, probably by proteolysis. The previous findings that spirochetes bind serum-derived plasminogen and that plasmin favors spirochetal invasiveness and infectivity suggested a role for plasmin in the pathogenicity of B. burgdorferi. Binding of plasminogen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 33 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…This implies that centrifugal spread of the migrating spirochete leads to colonization of the tissues. This is also supported by results of Klempner et al, who showed that B. burgdorferi possesses the ability to bind the host's plasminogen on its outer surface (17,25), which is enzymatically processed to surface-bound plasmin (13). Plasmin can degrade high-molecular-weight glycoproteins, which could improve the dissemination of B. burgdorferi in connective tissue.…”
Section: Discussionsupporting
confidence: 64%
“…This implies that centrifugal spread of the migrating spirochete leads to colonization of the tissues. This is also supported by results of Klempner et al, who showed that B. burgdorferi possesses the ability to bind the host's plasminogen on its outer surface (17,25), which is enzymatically processed to surface-bound plasmin (13). Plasmin can degrade high-molecular-weight glycoproteins, which could improve the dissemination of B. burgdorferi in connective tissue.…”
Section: Discussionsupporting
confidence: 64%
“…Using quantitative RT-PCR, we show that Borreliainduced transcription of uPA in monocytic cells terminates after 4 h of co-culturing with B. burgdorferi. This time frame of uPA transcriptional induction observed may require viable spirochetes as previous findings using lipidated OspA showed a delayed transcription of uPA that peaked at 4 h of stimulation (Fuchs et al, 1996). The degree of induction of levels and activity of uPA by B. burgdorferi appears to be in the same order as in clinical situations where different concentrations can be associated with progression of disease and as indicator of prognosis (Miyake et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…However, these experimental approaches are limited by ethical considerations as well as the fact that not all data can be applied to the situation in humans. Most in vitro studies are based on findings in monolayer cell cultures(14–19). The major shortcoming of these experimental settings is the loss of the physiologic 3‐D arrangement of the cells, which leads to changes in morphology and function.…”
Section: Discussionmentioning
confidence: 99%